TEACHING STRATEGIES FOR IMPROVING COGNITIVE AND EMOTIONAL SKILLS OF THE STUDENTS AT THE VETERINARY MEDICINE AND ANIMAL HUSBANDRY FACULTY, UPCH, PERU - Grandez R., Ricardo (2014)
The paper presents actions taken to modify the theoretical characteristics of the course of Medicine of Companion Animals, a mandatory course of the Veterinary Medi- cine and Animal Husbandry career at Universidad Peruana Cayetano Heredia, Lima, Peru. A practical-theoretical course was organized in pursuit of improving basic knowledge, skills and abilities in the veterinary field, and also for improving cognitive and emotional skills of students through innovative educational methodologies and technologies. These included resolution of clinical cases, critical thinking and creativity, revision, interpretation and analysis of scientific information, contextualized activities in actual practice, support of social activities and technology transfer of scientific information, all within a framework of university education by competences. The assessment of cognitive and emotional abilities was done by the Bar-On Emotional Quotient Inventory survey. A survey was conducted at the beginning and another at the end of the course involving 24 out of 30 registered students. The results show that the percentage of students with cognitive and emotional skills qualified as developed, adequate and to be improved was 25, 51 and 21% respectively in the first survey, and improving to 54, 33 and 13% respectively in the second survey.